Alcohol restriction in muslim friendly hospitality services: treat or opportunity? - Wan Shamsuddin, Wan Norshafiqah; Mahamod, Lukman Hakim; Hashim, Khairusy Syakirin Has-Yun; Ibrahim, Mansor; Othman, Rashidi (Universiti Teknologi Mara ( UiTM), 2016)
Muslim-friendly hospitality service is one of Islamic tourism products introduced to accommodate the increasing number of Muslim travellers. Islamic tourism is not just about Halal food, but also hospitality services that in line with the Islamic Law (Shariah). The dimension of Islamic law that covers hotels, resorts, restaurants and airlines industries including not provide alcoholic beverages, serve food with halal certificates and accommodate separate facilities for different gender, provide prayer facilities and a generally decorated with Muslim-friendly environment (Islamic Tourism Centre, 2015). This paper is a part of major research on Muslim-friendly compliant Tourism Accommodation Premises (TAP) in improving the Muslim-Friendly Hospitality Services (MFHS) Malaysian Standard. The paper used desks study as the method of the research. The study found that the top three (3) issues rise from the implementation of Muslim-friendly accommodations premises are profit, customer and star rating of the hotel. The aim of the research is to understand the issues arise from alcohol restriction in Malaysian tourism accommodations premises.